(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Predators attracted to the sex pheromones of Matsucoccus josephi Bodenheimer & Harpaz, M. feytaudi Ducasse, M. matsumurae Kuwana, and controls (without pheromones) in east Tennessee were collected from May 1999 through July 2000. Delta style sticky traps (n=60) baited with the sex pheromones of Matsucoccus spp. were placed in 5 pine sites along elevation gradients in the Great Smoky Mountains National Park. From 468 sticky inserts processed, 7,972 insect specimens representing 112 species, 83 families, and 12 orders were identified. Some 99% (n= 546) of all neuropterans and 88% (n =72) of all hemipterans were captured from pheromone traps, compared to the control traps. Hemerobiidae was represented by 510 specimens of Hemerobius stigma Stephens (= stigmaterus Fitch), two specimens of Sympherobius barberi Banks, and three specimens of Micromus posticus Walker. Highest numbers of individuals were captured in the sex pheromone traps of M. josephi (267), M. feytaudi (224), M. matsumurae (25), and the control (I), respectively. Signficantly high numbers of predators were captured at pine sites at Little Greenbriar Trail and Bullhead Trail on Mt. LeConte in traps baited with pheromones of M. feytaudi and M. josephi in stands of Pinus pungens, on dry, rocky ridges between 914m and 1392m. Twenty-five specimens of Elatophilus inimica were also captured from sites at Little Greenbriar Trail and Bullhead Trail on Mt. Leconte, University of Tennessee Arboretum, and Foothills Parkway sites. Of these, 14 were captured from pine site at Little Greenbriar Trail in traps baited with pheromones of M. matsumurae and M. feytaudi. These data suggest that E. inimica, like H. stigma, were most abundant in stands of P. pungens on dry, rocky ridges between 914m and 1392m. Collection of E. intimica represents new county and state records, and the southern-most distribution recorded for this species.